PENGENDALIAN PENCEMARAN UDARA LINTAS BATAS DALAM PERSPEKTIF PERJANJIAN INTERNASIONAL - Suparto Wijoyo (Universitas Airlangga, 2012)
International treaties in the field of protection of atmosphere and trans-boundary air pollution that qualified as ‘soft law’ and ‘hard law’ legal document has developed since 1919 until at present. From the Study on the International treaties, it can be known that the global community has strong commitment to the problem of protection of atmosphere and trans-boundary air pollution. Unfortunately, it can be concluded, that those international treaties is so fragmented and therefore, is difficult to be implemented comparing with instrument of international environmental law in general.Keyword: international treaties, protection of atmosphere, transboundary air pollution